Functional Poly(ε-caprolactone) Based Materials: Preparation, Self-assembly and Application in Drug Delivery - Xiao, Yan; Yuan, Ming; Zhang, Jun; Yan, Jinliang; Lang, Meidong (Current Topics in Medicinal Chemistry, 2014)
Recent advances in synthesis of functional poly-ε-caprolactone (PCL) and its self-assembly behavior, as well as application in drug delivery have been reviewed. Three strategies including end group functionalization, postpolymerization modification and new monomer preparation have been summarized to show possibilities for PCL derivatives. Complex architectures like cyclic and multi-arm PCL have been emphasized. Both chemical composition and topology have coordinately affected the property of PCL-based materials on the molecular level. A large variety of PCLs with sophisticated topology like block, graft, cyclic, and star have displayed versatile morphologies in solutions. These selfassembly aggregates have been applied as nano-scaled drug carries either to physically encapsulate or covalently conjugate drugs for controlled release. In particular, PCL with pendant groups has been extensively studied to illustrate the noncovalent interaction with drugs and the influence on the release profile. In general, functional PCL has shown great potential in construct of complicated supramolecular structures, and thus as ideal drug carriers for sustainable and targeted delivery.
Keywords: Functional poly-ε-caprolactone (PCL)